2009
DOI: 10.1086/648406
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Inactivated Split‐Virus Influenza Vaccine against Culture‐Confirmed Influenza in Healthy Adults: A Prospective, Randomized, Placebo‐Controlled Trial

Abstract: ClinicalTrials.gov identifier: NCT00363870.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 17 publications
0
37
0
1
Order By: Relevance
“…Here, we describe the use of a real-time PCR (rtPCR) assay 8 in conjunction with virus culture in a prospective influenza vaccine efficacy study. 14 …”
Section: Introductionmentioning
confidence: 99%
“…Here, we describe the use of a real-time PCR (rtPCR) assay 8 in conjunction with virus culture in a prospective influenza vaccine efficacy study. 14 …”
Section: Introductionmentioning
confidence: 99%
“…Non-inferiority of the newly-licensed vaccine in the elderly (≥65 years) was determined in the same way (secondary analysis). The primary immunogenicity analysis was based on the according to protocol (ATP) cohort, which included all evaluable subjects for whom post-vaccination assay results for antibodies the newly-licensed vaccine, 31 all US regulatory requirements for licensure of the new vaccine for use in adults have been completed.…”
Section: Discussionmentioning
confidence: 99%
“…For the healthcare workers group, we calculated a pooled estimate of vaccine efficacy amongst 10 studies [8][9][10][11][12][13][14][15][16][17] for healthy adults aged 18-49 and results of the meta-analysis showed that pooled estimate of vaccine efficacy was equal to 66% (CI: 60-72) and there was heterogeneity between the results of the studies (Q = 13.69, P = 0.250). Regarding the school-age children, 2 studies [18,19] were included and pooled estimate of the vaccine efficacy was 64% (CI: 51-76).…”
Section: Vaccine Efficaciesmentioning
confidence: 99%